2022
DOI: 10.1177/0271678x221109873
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Koizumi model of mouse cerebral ischemia: A comparative longitudinal study of cerebral and retinal ischemia in the Koizumi and Longa middle cerebral artery occlusion models

Abstract: Cerebral and retinal ischemia share similar pathogenesis and epidemiology, each carrying both acute and prolonged risk of the other and often co-occurring. The most used preclinical stroke models, the Koizumi and Longa middle cerebral artery occlusion (MCAO) methods, have reported retinal damage with great variability, leaving the disruption of retinal blood supply via MCAO poorly investigated, even providing conflicting assumptions on the origin of the ophthalmic artery in rodents. The aim of our study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…2 ). Although the sham operation is generally considered not to have any adverse effects, the findings from our own group show that the ligation of Common carotid artery during the sham procedure causes chronic hypoperfusion in the brain 25 .
Figure 2 Immunohistochemistry results of SATB2 in the mouse brains isolated 7 days after MCAO or Sham surgery.
…”
Section: Resultsmentioning
confidence: 66%
“…2 ). Although the sham operation is generally considered not to have any adverse effects, the findings from our own group show that the ligation of Common carotid artery during the sham procedure causes chronic hypoperfusion in the brain 25 .
Figure 2 Immunohistochemistry results of SATB2 in the mouse brains isolated 7 days after MCAO or Sham surgery.
…”
Section: Resultsmentioning
confidence: 66%
“…Neuronal apoptosis rate Helena, J. 2022 31 C57Bl6 mice (male, 3–6 months old) Isoflurane 1. Processing: tip coated with silicone 2.…”
Section: Resultsmentioning
confidence: 99%
“… 36 + + + + + + + 7 2019 Wang Dongliang 27 + + + + + 5 2021 Onufriev, M.V. 28 + + + + + + + 7 2022 Wang Wenxiu 29 + + + + + + 6 2022 Yang Zhong 30 + + + + + + + 7 2022 Helena, Justic 31 + + + + …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the retinal nerve fiber layer thickness might be a promising parameter for monitoring axonal loss in ocular and neurological diseases [ 3 , 4 ]. Studies in animal models have indicated that ischemic stroke induced by middle cerebral artery occlusion (MCAO), may lead to retinal functional impairment, particularly retinal layer thinning [ 1 , 5 , 6 ]. In addition, some clinical studies also demonstrated that retinal nerve fiber layer thickness was reduced in patients with cerebral infarction [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%